PENGARUH LATIHAN HEEL RAISES DUDUK DAN PANJANG TUNGKAI TERHADAP HASIL LOMPAT JAUH GAYA JONGKOK - Pujianto, Agus (Universitas Negeri Semarang, 2009)
This experimental research was aimed to find out: 1) the different effect between the exercise method of sit heel raises the feet on the block compared to onÃÂ floor towards the result of the tuck style long jump, 2) the different effect between long leg and short leg towards the result of tuck style long jump, 3) the interaction between the exercise method of sit heel raises and the length of leg toward the result of tuck style long jump. This is an experimental research. The result of the research hypothesis test was analyzed with Analysis of Variance (ANOVA) two ways with significance degree 95%, the result i.e: the first hypothesis test shows that the value of count is 12.29 higher than the F table as amount of 4.11 ( Fo=12.29> Ft=4.11 ). The summary: there is different effect between sit heel raises exercise with feet touches up on the block and the feet touches upon the floor toward the result of tuck style long jump. The second hypothesis test shows the value of F count is 17.97 higher than F table as amount 4,11 ( Fo=17.97 > Ft=4.11 ). The summary: there is different effect between long leg and short leg toward the result of tuck style long jump. The thirdhypothesis test shows F count 4.67 is greater than F table as amount 4.11 ( Fo= 4.67 > Ft=4.11 ). The summary: there is interaction between sit heel raises exercise and the length of leg towards result of tuck style long jump. The further analysis caused by significant Analysis of Variance between the method of sit heel raises exercise and the length of leg towards the result of tuck style long jump tested using F Scheffe test andthe result are as follows: a) Sit heel raises exercise with feet touches upon the block was proven to give a better effect comparing to sit heel raises exercise with feet touches upon the floor towards the result of tuck style long jump ( FSA=11.97>Ft=4.11), b) Long leg was proven to give a better effect comparing to short legs towards the result of tuck style long jump ( FSB=18.47 > Ft=4.11 ). Hopefully this research result will be useful for sport teacher and coaches who intend to develop long jump, if they want to create exercise program, sit heel raises exercise with feet touches upon the block involved in the alternative exercise, and should give interest in the length of leg, because in this research it was proven that long legs had abetter effect compared to short legs towards the result of tuck style long jump.Kata kunci: latihan heel raises duduk, panjang tungkai, lompat jauh gaya jongkok